P0392AHUS ASSOCIATED WITH IGA NEPHROPATHY. (6th June 2020) - Manenti, Lucio; Delsante, Marco; Pisani, Isabella; Ricco, Federico; Gentile, Micaela; Fiaccadori, Enrico
Abstract: Background and Aims: IgAN is characterized by the presence of intense deposits of C3 accompanying IgA. As documented in several studies this is due to the activation of the complement system by pathological IgA; the mechanism of IgA–mediated complement activation remains poorly understood but is thought to act with different mechanisms such as the stabilization of the C3 convertase, the activation of the lectin pathway through polymeric IgA and eventually inherited partial deficiencies of complement regulatory genes [Maillard N, Wyatt RJ, Julian BA, Kiryluk K, Gharavi A, Fremeaux-Bacchi V, Novak J.J Current Understanding of the Role of Complement in IgA Nephropathy.Am Soc Nephrol 26:, 2015] . Dysregulation of the C3 convertase is a recognized cause of thrombotic microangiopathy (TMA) in atypical hemolytic uremic syndrome (aHUS). The association between aHUS and IgAN has been sporadically described . In this study we report a series of 6 patients, observed in our department, with biopsy proven IgAN, who developed aHUS during the follow-up. We report a series of aHUS associated IgA nephropathy. Method: This report describes 6 patients with aHUS IgAN who were identified among all patients with biopsy proven IgAN observed at the Department of Nephrology, University of Parma, from March 2010 to March 2015. The diagnosis of aHUS was suspected in the presence of renal biopsy with documented typical signs of TMA (glomerular or arteriolar thrombi, onion skin lesions) associated with non-immune microangiopathic haemolytic anemia, increased reticulocyte count, negative Coomb test, thrombocytopenia (platelets <150000/mm3). Results: Data collected on the 6 patients with IgA nephropathy associated with aHUS are described in Figure 1. All the cases of aHUS-IgAN were characterized by worsening of nephrotic proteinuria and reduced serum C3. Pathogenetic variant of CFH, predisposing for aHUS were identified in 2/6 cases; in the remaining patients a predisposing risk aplotype for aHUS was documented. All patients were treatment resistant for IgA nephropathy, had persistent proteinuria and progressed to ESRD. Conclusion: It is known that most cases of aHUS are associated with the presence of genetic or acquired alterations of the regulation of the complement AP. However overlapping of other triggering conditions was documented in 70% of aHUS cases [Noris M, Caprioli J, Bresin E, et al. Relative Role of Genetic Complement Abnormalities in Sporadic and Familial aHUS and Their Impact on Clinical Phenotype. Clin J Am Soc Nephrol. 2010;5: 1844–1859]. Our case series shows that the presence of genetic factors predisposing to uncontrolled activation of the C3 convertase associated to continuous activation of the same enzyme from pathological IgA, could lead to sC3 consumption, development of aHUS and consequent rapid progression towards ESRD. In conclusion during the natural history of IgAN, appearance of hemolysis, thrombocytopenia, serum C3 reduction and increasing proteinuria would suggest to search for aHUS, allowing to early treatment with plasmapheresis and/or new available complement targeted inhibitors to prevent renal failure.